The theory of implementation of social choice rules - Roberto Serrano (Brown University, Department of Economics, 2003)
Suppose that the goals of a society can be summarized in a social choice rule, i.e., a mapping from relevant underlying parameters to final outcomes. Typically, the underlying parameters (e.g., individual preferences) are private information to the agents in society. The implementation problem is then formulated: under what circumstances can one design a mechanism so that the private information is truthfully elicited and the social optimum ends up being implemented? In designing such a mechanism, appropriate incentives will have to be given to the agents so that they do not wish to misrepresent their information. The theory of implementation or mechanism design formalizes this “social engineering” problem and provides answers to the question just posed. I survey the theory of implementation in this article, emphasizing the results based on two behavioral assumptions for the agents (dominant strategies and Nash equilibrium). Examples discussed include voting, and the allocation of private and public goods under complete and incomplete information.
Keywords: C72; D78; D82; 330; Implementation theory; mechanism design; asymmetric information; Decentralization; game theory; dominance; Nash equilibrium; monotonicity; Public Choice; Unvollkommene Information; Nash-Gleichgewicht; Theorie